Effect of polysaccharides from Tremella fuciformis on UV-induced photoaging. (January 2016) - Wen, Lingrong; Gao, Qing; Ma, Chung-wah; Ge, Yazhong; You, Lijun; Liu, Rui Hai; Fu, Xiong; Liu, Dong
Highlights: Antioxidant polysaccharides (TP) rich in uronic acid were prepared in this study. TP reduced the skin water and collagen losses induced by UV radiation. TP ameliorated the skin structure alterations caused by skin photodamage. TP increased the activities of SOD, GSH-Px and CAT. TP's skin protective effect was related with its antioxidant activity. Abstract: Tremella fuciformis Berk, a popular nutritious mushroom in China, has attracted increasing attention due to its various bioactivities. In the present work, T. fuciformis polysaccharides (TP) were extracted with hot water. It mainly consisted of mannose, as well as 10.77% (w/w) uronic acid. In additional, the anti-photoaging effects of TP were evaluated using a 30-day UV-irradiated animal assay. TP could efficiently reduce the water and collagen losses of the skin, and inhibit the increase of glycosaminoglycans. Moreover, a histopathological study showed that, UV-induced skin structural alterations were alleviated as well as repairing endogenous collagen breakdown and maintaining the ratio of type I/III collagen, after oral treatment of TP. The activities of SOD, GSH-Px and CAT were increased compared to the irradiated control group without treatment. Accordingly, TP can be used as a potential functional food supplement for skin function protection.